Performances Analysis in an Islamic Boarding School: Insights From Indonesia - Sari, Niki Puspita; Muhammad, Helmi; Umam, Khairul (Fitrah: Journal of Islamic Education, 2023)
Employee performance is an important factor in determining organizational success. Previous studies on employee performance are dominated by the business sector. Whereas the performance of non-business organizations such as Islamic boarding schools also requires administrators to provide high performance as business organizations. Along with modern developments, Islamic boarding schools are required to adapt to a new environment that allows pressure on the management. The demands of adaptive Islamic boarding schools also allow administrators to feel like or dislike their work. This study aims to analyze the performance in Islamic boarding schools influenced by the variables of stress and job satisfaction. Data were collected through questionnaires distributed to 60 administrators of Miftahul Ulum Islamic Boarding School, Malang, Indonesia, using the census method and analyzed by multiple linear regression. The results showed that job stress had a significant effect on the performance of Miftahul Ulum Islamic boarding school administrators. However, job satisfaction has no significant effect on the performance of Miftahul Ulum Islamic boarding school administrators. The results of this study have positive implications for the leadership of Islamic boarding schools to improve performance through human resource management.